The Identification of River Flow Capacity using the HEC-RAS 1D Model: Case Study of Sringin River Downstreamdy of the Sringin River Downstream - Ikhwanudin, .; Afifah, Risdiana Cholifatul; Husodo, Ibnu Toto; Yudaningrum, Farida (Aceh International Journal of Science and Technology, 2024)
The Sringin is a downstream river located in East Semarang. The Sringin River becomes the channel waste of the East Semarang district area. The Sringin River bank is surrounded by the Terboyo industrial area and settlement. The flood occurred in both areas, especially at Ngilir village, Genuk subdistrict. It is caused by low-capacity sedimentation channels and buildings occupying the channel body. The study aims to estimate flood discharge during repeat period 2, 5, 10, 25, 50, and 100 years on Sringin river downstream, analyze the capacity cross-section river, and identify the river water level profile when debit flowed with various period repeat flood. The hydrology calculation showed that flood discharge plans in the repeat period 2, 5, 10, 25, 50, and 100 years are 12.42; 16.67; 19.81; 30.7; 31.6; 33.22 m 3 /s. At the same time, the flow river capacity is 2.95 m/s in the upstream section and 15.52 m/s in the downstream section. Thus, floods occurred in some places when large discharges flowed. In period 2, the water level is about 1.0 to 1.5 meters. In more repeat periods, the level is higher. The conclusion is that the Sringin River cannot flow with perfect discharge, which exceeds its flow capacity.